Integrating empirical analysis into analytical framework: An integrated model structure for on-demand transportation - SU, Yuliu (Institutional Knowledge at Singapore Management University, 2021)
On-demand transportation services have been developing in an irresistible trend since their first launch in public. These services not only transform the urban mobility landscape, but also profoundly change individuals’ travel behavior. In this paper, we propose an integrated model structure which integrates empirical analysis into a discrete choice based analytical framework to investigate a heterogeneous population’s choices on ownership, usage and transportation mode with the presence of ride-hailing. Distinguished from traditional discrete choice models where individuals’ choices are only affected by exogenous variables and are independent of other individuals’ choices, our model extends to capture the endogeneity of supply demand imbalance between ride-hailing service providers and users. Through equilibrium searching and counterfactual analysis, we further quantify the magnitude of impacts of platform operations and government policies on car demand, usage and traffic. The structure of the model and managerial insights are explained in detail.